Understanding the daily to decadal evolution of mountain glaciers in Alaska and high mountain Asia from satellite remote sensing - Zeller, Lucas R., author; McGrath, Daniel, advisor; Gallen, Sean, committee member; Ross, Matthew, committee member; Florentine, Caitlyn, committee member (Colorado State University. Libraries, 2024)
Glaciers are important components of mountain ecosystems, mountain hydrological systems, and the global water cycle. Improving our scientific understanding of the spatial and temporal variability in glacier changes and the physical processes that drive those changes will allow better prediction of future glacier evolution. In this dissertation, I explore ways in which satellite-based remote sensing products can be used to study mountain glaciers across a wide range of spatial and temporal scales, with a specific focus on Alaska and High Mountain Asia. The accumulation area ratio (AAR) of a glacier reflects its current state of equilibrium, or disequilibrium, with climate and its vulnerability to future climate change. In Chapter 1, I present an inventory of glacier-specific annual accumulation areas and equilibrium line altitudes (ELAs) for over 3,000 glaciers in Alaska and northwest Canada (88% of the regional glacier area) over the 2018–2022 period derived from Sentinel-2 satellite imagery. I find that the five-year average AAR of the entire study area is 0.41, with an inter-annual range of 0.25–0.49. More than 1,000 glaciers, representing 8% of the investigated glacier area, were found to have effectively no accumulation area. Summer temperature and winter precipitation from ERA5-Land were found to be effective predictors of inter-annual ELA variability across the entire study area (R2=0.47). An analysis of future climate projections (SSP2-4.5) shows that ELAs will rise by 170 m on average by the end of the 21st century. Such changes would result in a loss of 25% of the modern accumulation area, leaving more than 1,900 glaciers (22% of the investigated area) with no accumulation area. These results highlight the current state of Alaska glacier disequilibrium with modern climate, as well as their vulnerability to projected future warming. In High Mountain Asia, many glaciers have thick debris cover over the majority of their ablation zones, earning them the name 'debris-covered glaciers'. Supraglacial lakes (SGLs) play an important role in debris-covered glacier (DCG) systems by enabling efficient interactions between the supraglacial, englacial, and subglacial environments. Developing a better understanding of the short-term and long-term development of these features is needed to constrain DCG evolution and the hazards posed to downstream communities, ecosystems, and infrastructure from rapid drainage. In Chapter 2, I present an analysis of supraglacial lakes on eight DCGs in the Khumbu region of Nepal by automating SGL identification in PlanetScope, Sentinel-2, and Landsat 5–9 satellite images. I identify a regular annual cycle in SGL area, with lakes covering approximately twice as much area during their maximum annual extent (in the pre-monsoon season) than their minimum annual extent (in the post-monsoon season). The high spatiotemporal resolution of PlanetScope imagery (∼ daily, 3 m) shows that this cycle is driven by the appearance and expansion of small lakes in the upper debris-covered regions of these glaciers throughout the winter. Decadal-scale expansion of large, near-terminus lakes was identified on four of the glaciers (Khumbu, Lhotse, Nuptse, and Ambulapcha), while the remaining four showed no significant increases over the study period. The seasonal variation in SGL area is of comparable or greater magnitude as decadal-scale changes, highlighting the importance of accounting for this seasonality when interpreting long-term records of SGL changes from sparse observations. The complex spatiotemporal patterns revealed in this analysis are not captured in existing regional-scale glacial lake databases, suggesting that more targeted efforts are needed to capture the true variability of SGLs on large scales. In Chapter 3, I expand these methods across a wider spatial extent by using the Landsat 5, 7, 8, and 9 archive to delineate SGLs on debris-covered glaciers across all of High Mountain Asia at near-annual cadence from 1988–2023. I find that SGL area has increased throughout the study period, rising to 17.2 km2 (0.7% of the investigated debris-covered area) in 2023, compared to ~8 km2 (0.3% of debris-covered area) in 1988. SGL growth is most concentrated in the Himalaya and Nyainqêntanglha regions, which have also experienced the greatest rates of 20th and 21st century mass loss. The 21st century SGL growth is concentrated almost entirely near the termini of these glaciers, indicating the possibility of continued growth and coalescence into large proglacial lakes. Areas of high SGL concentration are predominantly found in areas with lower surface gradients, low velocity, and thicker debris cover. Glaciers with high SGL concentrations are found to have steeper longitudinal gradients of thinning, with greater thinning rates further from the terminus resulting in lower surface slopes and more concave geometries throughout their entire debris-covered extents. However, the representative longitudinal thinning pattern of glaciers without substantial SGL formation have become more similar to this pattern in recent years, suggesting that more of these glaciers may be primed for SGL formation in the future.